Development, Optimization and Absorption Mechanism of DHP107, Oral Paclitaxel Formulation for Single-Agent Anticancer Therapy - Lee, In-Hyun; Hong, Jung Wan; Jang, Yura; Park, Yeong Taek; Chung, Hesson (IntechOpen, 2012)
None